Subtalar Nonunion Following Tibiotalocalcaneal Fusion Using an Intramedullary Nail: A Case Series of Errant Entry Points. Issue 4 (16th October 2019) - Martella, Anthony; Yue, Ruixian; Boin, Michael; Rogozinski, Jonathan; Flanigan, Trenden; Purcell, Kevin; Laughlin, Richard
Category: Hindfoot Introduction/Purpose: Tibiotalocalcaneal (TTC) arthrodesis is a procedure used to treat hindfoot deformity and/or arthritis. Retrograde intramedullary nails have been used as a method of fixation. The nails are either straight or have a bend to accommodate valgus alignment of the hindfoot. Studies comparing nail types or analysis of nonunions are lacking in the available literature on the subject despite a reported nonunion rate of up to 20%. The purpose of this study was to report a series of subtalar nonunions that all had an entry point that was too medial on the calcaneus resulting in inadequate purchase of the nail in the calcaneus. Methods: Six cases of subtalar nonunion were retrospectively reviewed. All were referred for second opinion. Evaluation consisted of examination, radiographs and CT scans. Patient demographics, comorbidities and findings common to all cases were recorded. Results: Presenting complaints in all cases were persistent swelling. Non-neuropathic cases all had hindfoot pain. In this series, all the implants were straight nails. Radiographs and CT scans revealed that all cases were done for severe valgus deformity with subtalar subluxation. In each of the cases, the deformity was under corrected and the nail entry point was too medial on the calcaneus which resulted in reaming out the medial wall of the calcaneus, decreasing the amount of fixation obtained with the nail. In each of the cases, the medial wall of the calcaneus was deficient and the nail had no medial containment. Conclusion: Severe valgus deformity with subtalar subluxation is a risk factor for subtalar nonunion when the deformity is under corrected and a straight nail is used. Ensuring that the tibia talus and calcaneus are collinear and that the entry point in the calcaneus is sufficiently lateral are important factors to consider when addressing this type of deformity. Accurate intraoperative imaging is essential to ensure proper positioning of the entry point to avoid reaming out the medial wall of the calcaneus and to ensure adequate purchase of the nail in the calcaneus.